Sistem Informasi Monitoring Pembayaran Piutang Penjualan Berbasis Web - Meri Mayang Sari; Tuti Nurhaeni; Abdul Musonip (IJAcc, 2023)
Progress and development of information technology occur quickly. This encourages business entities or companies to use information technology to support the development of employee performance to make it easier and more efficient. The application of information systems in various fields is now also widely used, one of which is in the field of accounting. However, not all companies have implemented a web-based information system, one example at PT. Sarana Anugerah Perdana. Problems that occur at PT. Sarana Anugerah Perdana is a credit payment monitoring system that still uses semi-computerization so that A.R staff have difficulty distinguishing which customer receivables are due or are due. Based on the background of the problem, the authors want to create a web-based monitoring system at PT. Sarana Anugerah Perdana. This research was conducted using the SWOT analysis method, system requirements elicitation and system design using UML (Unified Modeling Language) to visualize. In addition, the programming language used is PHP (Hypertext Preprocessor), database server with MySQL, sublime text 2, CodeIgniter framework and web server with XAMPP. With the existence of a system of monitoring the payment of accounts receivable, it can facilitate AR staff (Account Receivable) in monitoring customer receivables and also facilitate in making and producing payment reports and accurate accounts receivable.